Holding up the mirror: The impact of strategic procurement practices on account management - Ryals, Lynette; Rogers, B (Elsevier Science B.V., Amsterdam., 2006)
Procurement has grown up. It is now a strategic business function that increasingly recognizes the importance of strategic supplier relationships, a reflection of key account management. It is time to assess the impact of this shift on the profession and practice of account management. This paper examines customer adoption of strategic procurement and then discusses the implications this has for account managers at the suppliers serving these customers. New techniques are emerging in these special relationships, including the use of psychological contracts and co-measurement and monitoring. Perceived fairness will also have a major impact on the customer's view of their suppliers. Account managers must recognize these changes or fall victim to supplier delusion: the belief that they are performing better than they really are.
Keywords: Procurement; Key account management; Supply chain relationships